1998
DOI: 10.1101/gad.12.19.3044
|View full text |Cite
|
Sign up to set email alerts
|

Yeast telomeres exert a position effect on recombination between internal tracts of yeast telomeric DNA

Abstract: In Saccharomyces cerevisiae, proximity to a telomere affects both transcription and replication of adjacent DNA. In this study, we show that telomeres also impose a position effect on mitotic recombination. The rate of recombination between directly repeated tracts of telomeric C 1-3 A/TG 1-3 DNA was reduced severely by proximity to a telomere. In contrast, recombination of two control substrates was not affected by telomere proximity. Thus, unlike position effects on transcription or replication, inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 102 publications
1
32
0
Order By: Relevance
“…pombe. In contrast, sir mutations in budding yeast, which abrogate the position-effect control of transcription at the telomere (Gottschling et al, 1990) and enhance the accessibility of telomeres to dam methylase (Gottschling, 1992), do not abrogate the recombination block at telomeres; rather, it is abrogated by mutations in recombination pathways such as Rad51 (Stavenhagen and Zakian, 1998). Although similar recombination events have not been reported in other organisms, the possibility of heterochromatin playing a role in suppressing recombination in other systems is not ruled out.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…pombe. In contrast, sir mutations in budding yeast, which abrogate the position-effect control of transcription at the telomere (Gottschling et al, 1990) and enhance the accessibility of telomeres to dam methylase (Gottschling, 1992), do not abrogate the recombination block at telomeres; rather, it is abrogated by mutations in recombination pathways such as Rad51 (Stavenhagen and Zakian, 1998). Although similar recombination events have not been reported in other organisms, the possibility of heterochromatin playing a role in suppressing recombination in other systems is not ruled out.…”
Section: Discussionmentioning
confidence: 76%
“…Studies in the budding yeast have shown that heterochromatin regulates the telomere position effect, but surprisingly has no effect on telomere recombination; rather, aberrant recombination was reported in mutants in the Rad50 pathway (Stavenhagen and Zakian, 1998). In human cells, mutations in the histone methyltransferases Suv39h1 and Suv39h2 genes have been found to elicit telomere repeat elongation (Garcia-Cao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Allelic recombination was not altered significantly when leu2 heteroalleles were placed at proximal subtelomeric and interstitial loci (Lichten and Haber 1989) and between direct repeats placed at subtelomeric and interstitial loci (Stavenhagen and Zakian 1998). We have proposed a model where a recombination barrier is set up between subtelomeric and interstitial sequences via nuclear tethering based on sequence analysis and preliminary recombination studies .…”
Section: Resultsmentioning
confidence: 99%
“…44) or by the addition or removal of methyl groups (as in bacterial-style restriction-modification systems). Alteration of chromatin configuration similar to position effects on transcription (42,45) is a third possibility.…”
Section: Discussionmentioning
confidence: 99%